An ebsd study of nickel sheets after unidirectional and cross rolling arb processings - Duan, J.; Quadir, Md Zakaria; Ferry, M. (2015)
Copyright © 2015 MS&T15®.Commercially pure nickel sheets were processed by accumulative roll bonding (ARB) up to six cycles at room temperature in two different routes. In route one ARB was carried out conventionally and it is called U (unidirectional)-ARB. In route two the sample is rotated by 90° around the normal direction (ND) in alternating ARB cycles and it is called C (cross-rolled)-ARB. Both routes produce typical fine lath structures of severe rolling deformations. EBSD study shows that U-ARB produces typical FCC rolling textures containing Copper {112} <111>, S {123} <634> and Brass {110} <112> orientations. In comparison, C-ARB produces diffused orientation distributions with principal components distributing between Brass and {011} <111> orientations. Schmid factor calculation of the sheet around the RD shows less variation in C-ARB sample than the U-ARB sample. This implies that reduced in-plane anisotropics can be achieved by cross rolling in ARB processing.